2018
DOI: 10.1002/cpp.2336
|View full text |Cite
|
Sign up to set email alerts
|

What happens when the therapist leaves? The impact of therapy transfer on the therapeutic alliance and symptoms

Abstract: Background The therapeutic alliance is an important factor in psychotherapy, affecting both therapy processes and outcome. Therapy transfers may impair the quality of the therapeutic alliance and increase symptom severity. The aim of this study is to investigate the impact of patient transfers in cognitive behavioural therapy on alliance and symptoms in the sessions after the transfer. Method Patient‐ and therapist‐rated therapeutic alliance and patient‐reported symptom severity were measured session‐to‐sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(70 reference statements)
1
4
1
Order By: Relevance
“…As hypothesized, in this study of 23 adult community clients in individual open-ended psychodynamic psychotherapy who transferred from one therapist to another when doctoral student therapists left the clinic, clients on average rated the working alliance as worse with the posttransfer therapist than the pretransfer therapist. This aligns with prior findings that clients’ working alliance, contentment in therapy, and psychological health were lower after transfers (Sauer et al, 2017; Zimmermann et al, 2019). Thus, it supports the theory that therapists experience challenges in helping transferred clients to develop a working alliance with a new therapist (Barrett et al, 2008; Cox, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As hypothesized, in this study of 23 adult community clients in individual open-ended psychodynamic psychotherapy who transferred from one therapist to another when doctoral student therapists left the clinic, clients on average rated the working alliance as worse with the posttransfer therapist than the pretransfer therapist. This aligns with prior findings that clients’ working alliance, contentment in therapy, and psychological health were lower after transfers (Sauer et al, 2017; Zimmermann et al, 2019). Thus, it supports the theory that therapists experience challenges in helping transferred clients to develop a working alliance with a new therapist (Barrett et al, 2008; Cox, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Using Tau- U analysis, also, we could not determine whether there was a recovery in the working alliance over time. Given Zimmermann et al’s (2019) finding that after average five sessions, posttransfer therapist-rated working alliances became similar levels with working alliances rated by the pretransfer therapists, it would be interesting for a future study to explore how therapist attachment styles would predict a recovery in the client-rated working alliance. Another limitation is that our findings may be limited to adult clients and therapist trainees in open-ended individual psychodynamic psychotherapy in a doctoral-level training clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research has highlighted that in offender therapy it is crucial to take one's time to overcome mistrust to establish an effective alliance (Marshall and Serran, 2004;Goulet et al, 2019). This might be a particularly important aspect in therapy with persons in detention, as research in the community has shown that patients build up comparable alliance levels after three to five sessions on average (Zimmermann et al, 2019), in contrast, our participants' indicated taking three to 6 months time. It might be particularly difficult to build a strong alliance with patients suffering from substance use or personality disorders (Ross et al, 2008;Meyer et al, 2019), two highly prevalent disorders within the correctional context (Fazel et al, 2016).…”
Section: Discussioncontrasting
confidence: 58%
“…To receive optimal therapy, children have to develop a certain degree of connection with a therapist (McIntyre & Barton, 2010). In a field in which frequent rotation of therapists is a norm, a lot of time is wasted on the initial therapist-child bridge-building (Zimmermann et al, 2019). MITA, on the other hand, has only a minimal break-in period.…”
Section: )mentioning
confidence: 99%